2013
DOI: 10.6061/clinics/2013(02)oa21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the phytoestrogen genistein on the development of the reproductive system of Sprague Dawley rats

Abstract: OBJECTIVES:Genistein is known to influence reproductive system development through its binding affinity for estrogen receptors. The present study aimed to further explore the effect of Genistein on the development of the reproductive system of experimental rats.METHODS:Eighteen post-weaning female Sprague Dawley rats were divided into the following groups: (i) a control group that received vehicle (distilled water and Tween 80); (ii) a group treated with 10 mg/kg body weight (BW) of Genistein (Gen 10); and (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 49 publications
2
35
0
1
Order By: Relevance
“…Moreover, the lowest (75 mg/ kg) dose of C. adansonii extract turned to be more efficient than the higher one (300 mg/kg). This may be due to the saturation of estrogen receptors by bioactive compounds present in the extract which consequently will lead to the phenomena of down regulation of receptor induced by the higher dose of the extract; this phenomenon is common with phytoestrogen (Zin et al, 2013).…”
Section: Organsmentioning
confidence: 98%
“…Moreover, the lowest (75 mg/ kg) dose of C. adansonii extract turned to be more efficient than the higher one (300 mg/kg). This may be due to the saturation of estrogen receptors by bioactive compounds present in the extract which consequently will lead to the phenomena of down regulation of receptor induced by the higher dose of the extract; this phenomenon is common with phytoestrogen (Zin et al, 2013).…”
Section: Organsmentioning
confidence: 98%
“…Such studies have shown that embryonic or neonatal exposures to genistein cause the development of multi-oocyte follicles, increase atresia (Medigovic et al ., 2012), and reduce fertility in rodents (Britt et al ., 2005; Jefferson et al ., 2005; Chen et al ., 2007; Jefferson et al ., 2007; Jefferson et al ., 2009; Cimafranca et al ., 2010; Zhuang et al ., 2010). In addition, one study indicates that exposure to genistein after weaning alters circulating estradiol levels in rats, with the lower dose (10 mg/kg for three weeks) increasing estradiol levels and the higher dose (100 mg/kg for three weeks) inhibiting estradiol levels (Zin et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Genistein inhibits steroidogenesis or steroidogenic enzymes in cultured rat pre-antral follicles (Myllymaki et al ., 2005), rat granulosa-luteal cells (Whitehead and Lacey, 2000), and porcine granulosa, theca, or luteal cells (Gregoraszczuk et al ., 1999; Nynca and Ciereszko, 2006; Tiemann et al ., 2007; Basini et al ., 2010). Exposure to genistein also alters follicle growth (Zhuang et al ., 2010), induces follicular atresia (Zin et al ., 2013), and inhibits oocyte maturation (Chan, 2009). However, these studies have not examined the effects of genistein on the intact, adult antral follicle, the functional unit of the ovary.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a competition between estrogens and phytoestrogen is attributed to estrogen receptors, and in addition to estrogenic properties, antiestrogenic properties of plants on reproductive system can also be observed 34 . In general, phytoestrogens do not appear to have strong phytoestrogenic properties, and even their application does not show adverse and antiestrogenic effects in cases where the endometrial thickness is normal 29 .…”
Section: Erzhi Pilland Siwu Decoctionmentioning
confidence: 99%
“…Estrogen increases endometrial thickness by affecting glands and endometrial cells and increasing the blood flow of the functional layer. Besides, in plants, phytoestrogens can also increase endometrial thickness by imitating estrogens functions and binding to alpha-type estrogen receptor (ER-α) 34 .…”
Section: Erzhi Pilland Siwu Decoctionmentioning
confidence: 99%